PERMASALAHAN PENGELOLAAN GURU HONORER PADA JENJANG PENDIDIKAN DASAR - Sili Sabon, Simon (Jurnal Penelitian Kebijakan Pendidikan, 2022)
Honorary teachers are recruited to address the shortage of teachers in public schools, but the recruitment appears to be poorly planned. This hasty recruitment process results in inefficiency in the management and development of these honorary teachers. This qualitative research aims to describe and analyze the management of honorary teachers to support the optimization of school performance in primary education. This research used two methods of data collection, which are focus group discussions (FGD) and questionnaire. The data from the FGD were collected from honorary teachers and headmasters from several schools in West Java and Banten. And the data from the questionnaire were collected from 2.831 honorary teahers in Indonesa. The analyses on honorary teacher’s issues were related to: (i) staff planning, (ii) recruitment process, (iii) career development; and (v) competence, performance, and welfare. From the analysis, the research recommended: (i) the staff planning and recruitment process should be managed directly by the regional education office, (ii) in recruiting honorary teachers to become government employees with a work agreement, it is best to apply affirmative rules that provide a sense of fairness, (iii) it is best to mention teachers’ names when inviting them to self-development activities in orderto prevent the principals from sending only civil servant teachers, (iv) the government needs to thoroughly consider the welfare of the honorary teachers.